Antibacterial properties of selected freshwater microalgae against pathogenic bacteria - Das, B K; Jyothirmayee, Pradhan (Indian Journal of Fisheries, 2016)
Aqueous, ethanolic and methanolic extracts from four selected freshwater microalgae, Euglena viridis, Chlorella vulgaris, Microcystis aeruginosa and Spirulina platensis were examined for antibacterial activity by single disk diffusion method. All four algae revealed antibacterial properties. Best results were shown by the ethanolic extracts of E. viridis against Vibrio alginolyticus, Vibrio harveyi, Pseudomonas putida and Escherichia coli. Aqueous extracts of C. vulgaris also possessed antibacterial properties.